(untitled) (American Journal of Islam and Society, 2013)
Between June 30th, the twenty-fourth anniversary of the Islamist military takeover in Sudan, and July 4th, Independence Day in the United States, something miraculous happened in the Middle East. Suddenly everyone was in agreement, and – almost – everyone was happy. President Bashar al-Assad was ecstatic. In an interview with the Baath Party’s newspaper Al-Thawra shortly after the army deposed Muhammad Morsi, Egypt’s first-ever freely elected civilian president, on July 3, Assad applauded the coup as marking “essentially the fall of political Islam.”1 In his lengthy interview, he categorized his enemies into two groups: those “who completely abandoned their identity and embraced a ‘Western Dream’ even with all its flaws” and those “who went in exactly the opposite direction and abandoned their identity and embraced religious extremism.”2 The latter he alternatively designated as “Wahhabis” or “Takfiris.” In the presumed bastions of Wahhabism in the Gulf, Morsi’s downfall was received with even more elation. Within days, Saudi Arabia, Kuwait, and the UAE pledged an aid package worth USD 12 billion to cash-strapped Egypt, showing how much they appreciated this outcome.3 And while Israel joined its sworn enemy Hamas in maintaining a guarded silence,4 its media (and some politicians) did not hide their glee at Morsi’s political demise.5 As usual, the Obama administration was either unable to make up its mind or was too embarrassed to say what it believed. But that was in itself a clear stance, since the United States was happy to permit its key allies to provide massive cash injections to the new army-backed regime. It also refrained from ...